2023
DOI: 10.3389/fphar.2023.1202379
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin mitigates high glucose-induced lifespan reduction by inhibiting insulin signaling in Caenorhabditis elegans

Abstract: In organisms, high glucose can cause several aspects of toxicity, including the lifespan reduction. Paeoniflorin is the major component of Paeoniaceae plants. Nevertheless, the possible effect of paeoniflorin to suppress high glucose toxicity in reducing lifespan and underlying mechanism are largely unclear. Thus, in this study, we examined the possible effect of paeoniflorin in suppressing high glucose (50 mM)-induced lifespan reduction and the underlying mechanism in Caenorhabditis elegans. Administration wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The akt-1/2 genes encode the kinase cascade in the insulin signalling pathway, which has been identified to be required for the control of longevity [54]. Liu et al observed a decrease in akt-1 and akt-2 expressions after paeoniflorin administration, which showed a beneficial effect on lifespan [55]. The sgk-1 encodes a threonine/serine protein kinase that is crucial in the cellular stress response, and is also thought to act similarly to akt-1/2 in lifespan control by phosphorylating and inhibiting the nuclear translocation of DAF-16/FoxO [56].…”
Section: Discussionmentioning
confidence: 99%
“…The akt-1/2 genes encode the kinase cascade in the insulin signalling pathway, which has been identified to be required for the control of longevity [54]. Liu et al observed a decrease in akt-1 and akt-2 expressions after paeoniflorin administration, which showed a beneficial effect on lifespan [55]. The sgk-1 encodes a threonine/serine protein kinase that is crucial in the cellular stress response, and is also thought to act similarly to akt-1/2 in lifespan control by phosphorylating and inhibiting the nuclear translocation of DAF-16/FoxO [56].…”
Section: Discussionmentioning
confidence: 99%
“…Their offspring were exposed to PS-NPs. L4440, an empty vector, functioned as the control [ 60 ]. DCL569 is a tool strain for the germline RNAi of genes.…”
Section: Methodsmentioning
confidence: 99%